IMPLEMENTATION OF AN ENTERPRISE RESOURCE PLANNING (ERP)-BASED WORKSHOP INVENTORY MANAGEMENT INFORMATION SYSTEM AT PT. ANUGRAH FAJAR REZEKI - Dewiyana; Nurmalawati; Muhammad Abdul Rahman (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Anugrah Fajar Rezeki is a palm oil processing company located in Merbau Dua village, Birem Bayeun sub-district, East Aceh Regency. This research focuses on designing a workshop inventory management information system . This research aims to design a system that is integrated with the workshop inventory management information system using Enterprise Resource Planning (ERP) and implementing the ERP system. The conclusion of the research is that this workshop inventory management information system can help the company, where the previous company policy in recording goods management can only be done one by one manually so it takes a long time, after implementing the ERP system the data is easier to input and is immediately updated automatically for real-time goods management so it does not take a long time . In addition, the implementation of this workshop inventory management information system is very helpful in the process of collecting, managing data and making better decisions so as to increase efficiency, effectiveness, and development in operational processes at PT. Anugrah Fajar Rezeki.